PO.4.75 The anti-BDCA2 antibody biib059 improves joint and skin manifestations in patients with SLE and both active arthritis and rash. (27th September 2022) - Van Vollenhoven, RF; Furie, RA; Kalunian, K; Werth, VP; Carroll, H; Huang, X; Musselli, C; Barbey, C; Franchimont, N
Abstract : Purpose: BIIB059, a humanised monoclonal antibody targeting BDCA2, significantly reduced total active joint count versus placebo at Week 24 in patients with SLE in Part A of a Phase 2 study (NCT02847598 ). Changes in both joint and skin disease activity were assessed post hoc in a subset of patients with both arthritis and rash at baseline. Methods: Adults with SLE diagnosis, active arthritis and skin manifestations were randomised to receive BIIB059 450 mg or placebo subcutaneously. This post-hoc analysis included patients with both arthritis and rash based on baseline SLEDAI-2K, or BILAG-2004 musculoskeletal and mucocutaneous Grades A or B at baseline. In contrast to the previously reported primary analysis, there was no additional requirement for either skin disease activity or joint counts at baseline. The proportions of patients who improved in both domains (defined as absence of arthritis and rash by SLEDAI-2K, or improvement by ≥1 grade in BILAG-2004 musculoskeletal and mucocutaneous systems) were assessed at Week 24. Total joint count (evaluated by 28-joint assessment) and CLASI-A scores were assessed at baseline and Week 24. Results: The total numbers of patients included in this analysis were 61 and 52 (SLEDAI-2K), and 54 and 44 (BILAG-2004) for the BIIB059 and placebo treatment groups, respectively. At baseline, mean total joint count ranged between 11 and 12, and mean CLASI-A score ranged between 10 and 11 in both subpopulations. At Week 24, the proportions of patients with neither arthritis nor rash by SLEDAI-2K were greater with BIIB059 than placebo, as were the proportions with improvements in the BILAG-2004 musculoskeletal and mucocutaneous domains ( Table 1 ). Mean changes in total joint count and CLASI-A score from baseline were numerically greater with BIIB059 than placebo in the respective subpopulations. Conclusions: Among patients with active SLE in both joints and skin, those receiving BIIB059 had greater improvements versus placebo in both manifestations. These data support the potential benefit of BIIB059 treatment for joint and skin manifestations in SLE. Acknowledgements: This study and analysis were funded by Biogen. Medical writing support was provided by Selene Medical Communications, funded by Biogen.